Kepastian Hukum terhadap Label dan Sertifiksasi Halal Produk Pangan Berdasakan Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal - Slamet Pribadi; Diana Fitriana (Universitas Kuningan, 2022)
The aim of this research is to find out and analyze the legal arrangements regarding labels and certification of Halal Food Products. This study uses a normative juridical approach. Normative legal research is a procedure and method of scientific research to find the truth based on legal scientific logic from a normative point of view. Research results are In the food industry, food is processed through various new processing techniques and methods by utilizing scientific and technological developments, so that it becomes a product that is ready for consumption Public. However, keep in mind that most of the world's food industry and food technology products do not apply the halal certification system. This raises concerns that in facing free trade at the regional, international and global levels, Indonesia is being flooded with food products and other products that contain or are contaminated with haram elements. In processing, storage, handling, and packing techniques, preservatives are used which are harmful to health or additives containing haram elements which are prohibited by Islam. Halal certification is a business ethic that producers should carry out as a halal guarantee for consumers. Apart from being a halal guarantee for consumers, halal labels provide economic benefits for producers including: (1) Can increase consumer confidence because halal is guaranteed, (2) Has a USP (Unique Selling Point), (3) Able to penetrate the global halal market, (4) Improving product marketability in the market, (5) Cheap investment when compared to revenue growth that can be achieved.